(untitled) (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2025)
Current software development requirements in the European Union (EU) and the United States (US) stipulate mandatory compliance with web accessibility standards. Software products that do not meet these requirements cannot be certified for use in government institutions, which effectively makes inclusiveness an integral condition for the quality and competitiveness of software systems. Ukraine, moving towards European integration and considering the growing number of people with disabilities as a result of the war, must actively integrate accessibility principles into the education and professional training of future software development specialists. The article analyses educational programs in specialization ’Software engineering’ at leading Ukrainian universities. The study makes it possible to identify a number of academic disciplines that are most relevant for the integration of web accessibility topics. These include ‘Web Application Programming’, ‘Human-Computer Interaction’ and ‘UI/UX Design’, ‘Software Quality and Testing’, ‘Software Requirements Analysis’, as well as academic disciplines covering multimedia and hypertext technologies. These courses are directly related to the practice of designing and implementing user interfaces, testing and quality assurance, which creates the most favorable conditions for incorporating knowledge about web accessibility. Special attention is paid to reviewing open educational electronic resources that can serve as a basis for developing educational content. Among them are the ‘Web Accessibility’ course on the Diia.Education platform, the international ‘Digital Accessibility Foundations’ course from W3C, and educational programs from Deque University and Coursera. Their use makes it possible to integrate proven methodologies and practical approaches into the educational process, supplementing academic discipline with modern materials.